Rhizome Versus Mycelium: The Postmodern Reticulum in Umberto Eco's Il nome della rosa and Il pendolo di Foucault (ENTHYMEMA, 2024)
In 1983, Umberto Eco published the essay “L’antiporfirio”, in the volume edited by Gianni Vattimo and Pier Aldo Rovatti entitled Il pensiero debole. This text marks a theoretical watershed between the author’s first two novels, Il nome della rosa (1980) and Il pendolo di Foucault (1988), allowing us to understand how the encyclopedic narrative that characterizes both works constitutes an interpretative strategy of reality. Not only that: what we want to highlight here is the different way in which Eco approaches the complexity of the world through the themes and the structure of the story. In Il pendolo di Foucault the Parisian adventures are an application of the diffusive idea of the rhizome, the matrix of Il nome della rosa corresponds rather to the organization of the mycelium, the underground filigree of fungi that stops where the organism has sufficient nutrients and the possibility of being cultivated by other living species, putting a barrier to the disorder of reality.
Keywords: Umberto Eco; Encyclopedia; Postmodernism; Rhizome; Mycelium